2019
DOI: 10.1016/j.brs.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of transcranial magnetic stimulation in pregnant women with major depressive disorder

Abstract: Right-sided, low frequency TMS was effective in reducing depressive symptoms in this sample of pregnant women. There may be a possibility that TMS is associated with late PTB although a larger sample size would be needed for adequate power to detect a true difference between groups. This study demonstrated that TMS is low risk during pregnancy although larger trials would provide more information about the efficacy and safety of TMS in this population. This trial shows that an RCT of a biologic intervention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 36 publications
1
57
0
2
Order By: Relevance
“…Five percent of the participans in the study experienced premature birth, but two have already shown signs of premature birth risk in a biomedical test and the average rate of women experiencing premature births worldwide is 9.1 to 13.4% [87], it is unlikely that the causal relationship that rTMS treatment causes premature births will be established and further research is required. It was con rmed that brachial exus injury was the only side effect that occurred in newborns, including premature births, and that it was not associated with rTMS treatment [59]. There were no actual side effects in the infant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Five percent of the participans in the study experienced premature birth, but two have already shown signs of premature birth risk in a biomedical test and the average rate of women experiencing premature births worldwide is 9.1 to 13.4% [87], it is unlikely that the causal relationship that rTMS treatment causes premature births will be established and further research is required. It was con rmed that brachial exus injury was the only side effect that occurred in newborns, including premature births, and that it was not associated with rTMS treatment [59]. There were no actual side effects in the infant.…”
Section: Discussionmentioning
confidence: 95%
“…There were a total of 11 selected literature related to the e cacy and safety of rTMS for PPD, of which 2 RCT studies [59,60], 4 NRS [61][62][63][64], and 5 case studies [64][65][66][67][68]. The total number of participants are 100, 83 of whom received activee rTMS treatment.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published randomized controlled trial ( N = 22) that was performed during the second or third trimester of pregnancy (randomized to either active or sham rTMS,1:1 ratio; 20 sessions; LFR; single train, 900 pulses per session, 100% MT), the authors reported rTMS to be safe and superior to sham stimulation on continuous outcomes. In a case series ( N = 29), authors reported a 41.4% and 20.7% response and remission rates, respectively, and the newborns had no abnormalities reported, all born at >36 weeks of gestational age, with mean Apgar scores of 8.1/8.8, with no abnormalities reported during a mean follow‐up of 3.7 years …”
Section: Special Populationsmentioning
confidence: 99%
“…Moreover, in a RCT of twenty-two women with MDD in the second or third trimester of pregnancy that received 20 sessions of TMS to the right dorsolateral prefrontal cortex at 1 Hz as a single train of 900 pulses per session at 100% motor threshold, demonstrated that TMS was effective in reducing depressive symptoms in this sample of pregnant women. However, there is a possibility that TMS could be associated with late preterm birth, although a larger sample size would be needed to detect it [100]. Finally, the effect of rTMS therapy on mood has also been observed in patients with fibromyalgia [101].…”
Section: Medical Evidence and Clinical Effectiveness Of Classic Rtms-mentioning
confidence: 99%